Reduplication of Mongondow Language - Donal Matheos Ratu; Mister Gidion Maru (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This study aims at describing the reduplication of Mongondow and its meanings. The method used in this research is descriptive method in taxonomy that is an elaboration by classifying elements of language according to hierarchical relationship. Data were obtained through primary and secondary data sources. Primary data were collected through interviews with five informants chosen from Tutuyan region, of Tombolikat village, who are active speakers of Bolaang Mongondouw language. Secondary data were gathered through a text study. The results show that the formation of Mongondow words can be done by reduplication, either whole or complete reduplication and partial reduplication consisting of reduplication of deletion on the word base, reduplication of initial syllable and affixed reduplication. The reduplication of Mongondow language has the following meanings: (1) to declare uncertain plurality, (2) to declare reciprocal meaning, (3) to declare collective and distributive meaning, (3) to declare command or advice, (4) to declare the tool, (5) to declare the place (6) to declare about superlative, (7) to declare about more quality, and (8) to state the meaning of an action done with pleasure or comfort.